Pertumbuhan Semai Sengon (Paraserianthes Falcataria (L.) Nielsen) Pada Media Tanah Bekas Tambang Kapur Dengan Penambahan Pupuk Kompos Dan NPK - Basuki Wasis; Siti Halimatus Sa'idah (Jurnal Silvikultur Tropika, 2019)
Limestone mining activities are damaging soil and enviroment. Revegetation becomes an obligation on every mining sites. Paraserianthes falcataria is one of many species that suitable to be planted in revegetation site. Adding compost and NPK fertilizer can improve soil’s condition. This research objective is to analyze the effect of compost and NPK fertilizer on Paraserianthes falcataria seedlings growth and the exact appropriate dosage for limestone mining’s soil condition improvement. The design used in this research is completely randomized design with two factors. The result shows that addtion of compost on tailing media doesn’t give major effect or statistically not significant on seedling growth of height, diameter, the amount of root nodules, and shoot-root ratio, but statistically significant on wet and dry weight of the seedlings. NPK fertilizer addition on tailing media is statistically significant on the seedling growth of diameter, wet weight, and shoot-root ratio, but not significant different on height, dry weight, and the amount of root nodules. Interaction between compost and NPK fertilizer on media gives effect only at 95% of confidence level. K1N5 sample (with 100 gram composts and 5 gram of NPK fertilizer) gives the best respond on seedling’s growth. Very high levels of Ca in the soil medium will be toxic to the Paraserianthes Falcataria plant.Keywords: Compost, limestone mining, NPK fertilizer, Paraserianthes falcataria